2020
DOI: 10.4254/wjh.v12.i11.1076
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen and hepatitis B core-related antigen kinetics after adding pegylated-interferon to nucleos(t)ids analogues in hepatitis B e antigen-negative patients

Abstract: BACKGROUND Hepatitis B e antigen-negative chronic hepatitis B patients under nucleos(t)ids analogues (NAs) rarely achieve hepatitis B surface antigen (HBsAg) loss. AIM To evaluate if the addition of pegylated interferon (Peg-IFN) could decrease HBsAg and hepatitis B core-related antigen (HBcrAg) levels and increase HBsAg loss rate in patients under NAs therapy. METHODS Prospective, non-randomized, open-label trial evaluating the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…IFN-I is used to treat various diseases, including hepatitis C ( 45 , 46 ) and B ( 47 ), multiple myeloma ( 48 ), polycythemia Vera ( 49 ), and are also tested for the treatment of COVID-19. Studies carried out with inhaled or intramuscularly administered IFN-α2b have demonstrated that treatment can accelerate viral clearance and reduce circulating IL-6 and CRP levels ( 50 ), in addition to preventing disease progression ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…IFN-I is used to treat various diseases, including hepatitis C ( 45 , 46 ) and B ( 47 ), multiple myeloma ( 48 ), polycythemia Vera ( 49 ), and are also tested for the treatment of COVID-19. Studies carried out with inhaled or intramuscularly administered IFN-α2b have demonstrated that treatment can accelerate viral clearance and reduce circulating IL-6 and CRP levels ( 50 ), in addition to preventing disease progression ( 51 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we consider that NA type should be considered for the monitoring after interruption. Another interesting point of our cohort was that 37% added-on Peg-IFN two years before EoT [17] . Patients with add-on Peg-IFN showed faster HBsAg decline despite no differences in HBsAg loss rate were found.…”
Section: Discussionmentioning
confidence: 93%
“…However, patients treated with TDF compared to those treated with ETV showed earlier VR (4 vs. 12 weeks; p < 0.001), SVR (12 vs. 30 weeks; p < 0.001) and CR (10 vs. 48 weeks; p = 0.14). In patients who had received Peg-IFN ( n = 19) [17] the add-on therapy was finished a median of 2.3 years before EoT and no differences in HBsAg loss rate were found (5.3 vs. 15.2%; p = ns). However, patients with add-on Peg-IFN showed faster ( −0.10 vs. −0.05 log10 IU/mL/year; p = 0.02) and greater HBsAg decline ( −0.74 vs. −0.46 log10IU/mL; p = 0.056).…”
Section: Hbsag Kinetics According To Hbv Genotype and Na Therapymentioning
confidence: 99%
See 2 more Smart Citations